Analisis Kompetensi Dan Performa Karyawan Divisi Tim Operasional PT Enam Pilar Selaras - Salsabil Zata Dini; Abdul Azis (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze employee competency in the Operational Team Division of PT Enam Pilar Selaras and its role in improving employee performance. A qualitative descriptive method was used, with data obtained through in-depth interviews, observation, and documentation involving the director, division head, and operational staff, analyzed using the Miles and Huberman interactive model. The results show that employee competency has not been fully optimal; employees generally understand standard operating procedures and demonstrate adequate discipline, yet technical skills such as accuracy, speed, and communication remain unevenly mastered, and miscommunication between shifts continues to affect coordination. These competency gaps are reflected in varying work quality, limited productivity due to overlapping responsibilities, and inconsistent long-term commitment, indicating that structured training and a continuous performance evaluation system are needed to strengthen employee performance.